The Benefits of Conditional Cash Transfers: Learning from the Recipients of PKH Aid in Alor, East Nusa Tenggara - Setiadi, Setiadi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
Conditional cash transfers in Indonesia is better known as the Keluarga Harapan Program (PKH). This program offers aid to poor members of society and is intended to break the poverty cycle through education and healthcare. This aid is granted continuously, with certain conditions that must be met by recipients. The question is to what extent usage patterns are linked to the program's conditioning and its social function for recipients, and how local contexts influence the program's institutional and functional conditioning. This conditioning and usage patterns cannot be separated from the social, ecological, and economic conditions of the local community. After making the desire changes to social welfare, this aid has other effects, particularly as related to social aspects. These involve the usage patterns and strategies of aid recipients in adapting the aid programs implemented by the government for community members who live in poverty. As such, this article is hoped to provide a better understanding and ease interpretation of the topic. Data for this research was collected from four villages in East Nusa Tenggara using qualitative methods (observation, interviews, FGDs) and an MSC approach. Bantuan tunai bersyarat di Indonesia lebih dikenal dengan Program Keluarga Harapan (PKH). Program ini memberikan bantuan pada kelompok masyarakat paling miskin dengan tujuan memutus rantai kemiskinan melalui aspek pendidikan dan kesehatan. Bantuan ini diberikan secara berkelanjutan dengan kondisi yang harus dipatuhi oleh penerima.Pertanyaannya adalah bagaimana pola pemanfaatan bantuan berkaitan dengan pengkondisian program PKH dan bagaimana fungsi sosial bantuan tersebut terhadap pesertanya. Bagaimana pengaruh konteks lokal bagi pengkondisian aspek sosial yang meliputi kelembagaan dan fungsional program. Pengkondisian ini berkaitan erat dengan pola pemanfaatan bantuan dan tidak bisa dilepaskan dari kondisi ekonomi, ekologis dan sosial masyarakat setempat. Kemudian selain membawa perubahan dan kesejahteraan yang diharapkan bantuan ini ternyata juga membawa dampak lain, terutama berkaitan dengan aspek sosial. Dampak ini berkaitan dengan pola pemanfaatan dan strategi penerima bantuan dalam rangka adaptasi terhadap sebuah program yang diterapkan oleh pemerintah kepada masyarakat sangat miskin. Oleh sebab itu tulisan ini diharapkan memberi gambaran yang menambah pemahaman dan penafsiran yang berkaitan dengan topik tersebut. Data dalam penelitian ini dikumpulkan dari empat desa di NNT dengan metode kualitatif antara lain observasi, wawancara, dan FGD dengan pendekatan MSC.